Short-Term and Long-Term Curative Effect of Partial Hepatectomy on Ruptured Hemorrhage of Primary Liver Cancer after TAE - Xiulin Xiao; Lin Zhou; Long Zhang; Zhiyuan Xu; Qixin Dai; Xiaohong Deng (Emergency Medicine International)
Objective. To observe the short-term and long-term curative effects of partial hepatectomy on ruptured hemorrhage of primary liver cancer after transcatheter arterial embolization (TAE). Methods. A total of 150 patients with primary liver cancer treated in the hospital were enrolled as research objects between February 2018 and February 2021, including 75 cases undergoing TAE in the TAE group and the other 75 cases undergoing elective partial hepatectomy after TAE in the combination group. The surgical related indexes (leaving bed time, discharge time, success rate of hemostasis, lesion clearance rate), mean arterial pressure (MAP), heart rate (HR), hemoglobin, and liver function indexes (serum alpha-fetoprotein (AFP), albumin (ALB), total bilirubin (TBIL)) before and after treatment, postoperative complications, survival rate, and recurrence rate at 1 year after surgery between the two groups were compared. Results. Compared with the TAE group, hospitalization time was shorter (P<0.05), the success rate of hemostasis and lesions clearance rate were higher in the combination group (P<0.05). After surgery, levels of HR and serum AFP were significantly decreased, while levels of MAP, hemoglobin, serum ALB, and TBIL were significantly increased in both groups. The levels of HR and serum AFP in the combination group were lower than those in the TAE group, while levels of MAP, hemoglobin, serum ALB, and TBIL were higher than those in the TAE group (P<0.05). There was no significant difference in the incidence of postoperative complications between the two groups (P<0.05). Compared with the TAE group, the recurrence rate was lower, and the survival rate was higher in the combination group at 1 year after surgery (P<0.05). Conclusion. Partial hepatectomy can effectively improve hemostatic effect and liver function in ruptured hemorrhage of primary liver cancer after TAE, increase survival rate, and reduce postoperative recurrence rate.